Adaptive automatic control system with PI-controller frequency tuning - Степанец, Александр Васильевич; Моторина, Дария Андреевна (Eastern-European Journal of Enterprise Technologies, 2014)
Application of adaptive control systems, based on selftuning controllers with a test periodic signal is considered in the paper. The main purpose of the study is to develop a new adaptive control algorithm since the technological process maintenance quality directly affects the automatic control system profitability. To implement the control algorithm, digital controllers, based on microprocessors, allowing to realize complex mathematical processing of the input data can be used. The methods for implementing the adaptive control systems with harmonic input signal, using the method of frequency-division of control channels and self-tuning are discussed. The method of quick adaptive tuning of one-loop local automatic control systems using test harmonic signal is given in the paper. The considered control object must have self-regulation properties and medium persistence. To identify the control object, modern error estimate prediction method used. The method is based on analyzing the properties of the system output signal and calculating PI-controller settings, guaranteeing aperiodic transient of the set parameters. When optimizing the PI-controller settings, direct quality indicators of transient of closed-loop control system are estimated. The results of developing the adaptive control algorithm can be applied in one-loop control systems with simple local technological objects, and can also serve as a basis for further research of control systems, which use harmonic signals to obtain more information about the control object